Reassessment of changes in leucocyte and serum ascorbic acid after acute myocardial infarction. Issue 1 (January 1978) - Vallance, B D; Hume, R; Weyers, E
Abstract : After an acute myocardial infarction, there is an apparent acute fall in leucocyte ascorbic acid associated with an acute rise in white blood cells and serum cortisol. The apparent fall in leucocyte ascorbic acid is the result of the granulocytosis which occurs after the infarction. Estimations of ascorbic acid disclose that the granulocyte contains approximately half the ascorbic acid of the lymphocyte. When the granulocytosis subsides, the new population of white blood cells is depleted of ascorbic acid for at least 56 days, reflecting tissue desaturation which can be corrected by ascorbic acid supplements. Tissue desaturation is also reflected in subnormal serum ascorbic acid levels which persist also unless ascorbic acid supplements are given. Observations on normal subjects given infusions of tetracosactrin (Synacthen) show that adrenal stimulation can produce a similar rise in white blood cells and an apparent fall in leucocyte ascorbic acid concentration with the exception that the serum ascorbic acid remains unaltered. Therefore, while adrenal stimulation can mimic 'stress' with regard to the changes in the white blood cells, tissue depletion of ascorbic acid as reflected in the white blood cells and serum after a myocardial infarction requires a focus of damaged tissue.